Iron ore-petcoke briquettes as complementary burden for blast furnaces - Beatriz Fausta Gandra; Arthur Felipe Lino Oliveira; Maurício Covcevich Bagatini; Eduardo Osório (Journal of Materials Research and Technology)
Self-reducing agglomerates as a ferrous burden is a sustainable alternative to reduce fuel consumption and enhance productivity in the blast furnace process. This study evaluated self-reducing briquettes using petcoke (PC) as a reducing agent in a reducing atmosphere, to assess their potential for blast furnace application. The briquettes were produced in a pilot plant with PC content ranging from 0 to 15% by mass in the mix and evaluated for mechanical strength, metallurgical properties, and morphology. Briquettes containing up to 10% by mass of PC (BRI10) exhibited satisfactory mechanical strength for use in small blast furnaces, along with high shatter and tumbler indices. An optimized feeding strategy, such as blending with sinter, is desirable to enable its use. Although the briquettes exhibited low compressive strength, they did not generate fines during testing, even at 15% by mass of PC. Porosimetry analysis showed that the addition of PC promotes a pore distribution that favors the reduction of the agglomerate. Metallurgically, the briquettes containing up to 10% by mass of PC met the blast furnace requirements. Optical microscopy and XRD analysis after reduction showed that metallic iron increased with the PC content of the briquettes.